2016
DOI: 10.1186/s13068-016-0544-8
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the thermostability and catalytic efficiency of a highly active β-glucanase from Talaromyces leycettanus JCM12802 by optimizing residual charge–charge interactions

Abstract: Backgroundβ-Glucanase is one of the most extensively used biocatalysts in biofuel, food and animal feed industries. However, the poor thermostability and low catalytic efficiency of most reported β-glucanases limit their applications. Currently, two strategies are used to overcome these bottlenecks, i.e., mining for novel enzymes from extremophiles and engineering existing enzymes.ResultsA novel endo-β-1,3-1,4-glucanase of GH16 (Tlglu16A) from the thermophilic fungus Talaromyces leycettanus JCM12802 was produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 55 publications
1
19
0
Order By: Relevance
“…The thermophilic fungus Talaromyces is well-known for producing various extracellular enzymes [ 13 , 14 ]. Considering the great potential of thermophilic β -glucosidases for application in the food and feed field, a novel GH3 β -glucosidase-encoding gene from the thermophilic Talaromyces leycettanus was overexpressed in Pichia pastoris in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…The thermophilic fungus Talaromyces is well-known for producing various extracellular enzymes [ 13 , 14 ]. Considering the great potential of thermophilic β -glucosidases for application in the food and feed field, a novel GH3 β -glucosidase-encoding gene from the thermophilic Talaromyces leycettanus was overexpressed in Pichia pastoris in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…6C , middle panel), and decreasing the negative surface charge of E230G ( Fig. 6C , right panel) may improve the stability of the enzyme to high temperature and low pH 49 50 51 . Metal ions can bind to proteins at some atoms, i.e., C and H, inhibiting enzymatic activity 52 53 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Extremophiles are excellent sources of novel enzymes that can retain their integrity and function under extreme reaction conditions (32). Talaromyces leycettanus JCM12802, a thermotolerant fungus, that has an optimal growth temperature of 42 °C, is the source of various thermostable hydrolases including β -mannanase (33), xylanase (34), β -glucanase (35), and α -Amylase (36). In this study, a novel aspartic protease precursor comprising of 424 amino acid residues was identified in Talaromyces leycettanus and was determined to be a member of the A1 family of aspartic proteases.…”
Section: Discussionmentioning
confidence: 99%